MENINJAU DESAIN KEBIJAKAN IDLE PROPERTY TAX UNTUK MENEKAN PERILAKU SPEKULATIF TERHADAP PROPERTI - Muhammad Harmaen Pasha; Riyan Wahyu Setiawan; Arfan Rubysalam Muharrom; Achmad Farhan (Jurnal Akuntansi dan Pajak, 2025)
In 2021, Indonesia's National Land Agency (Badan Pertanahan Nasional) reported that 1.2 million hectares of land were identified as idle, with 89,000 hectares officially designated as abandoned land. Meanwhile, a significant portion of the population still struggles to access property, such as land or housing, due to rising property prices, which escalate yearly. This situation exacerbates inequality in property ownership, as outlined in Indonesia's Agrarian Law (UU Agraria), which mandates the government to ensure equitable access to land and address ownership disparities. Drawing on practices from countries such as the Philippines, Cambodia, and South Korea, a potential solution to address idle property issues is the imposition of an idle property tax. This policy could be implemented through a surcharge mechanism or a piggyback system on the existing Land and Building Tax (PBB-P2) based on the property’s assessed value (NJOP). A progressive tax rate could also be introduced, increasing with the duration a property remains idle. Such measures aim to deter speculative behavior that treats property solely as an investment without societal contribution. However, implementing this policy requires careful consideration of institutional harmonization, the overall tax burden, and the administrative costs to ensure an effective and balanced approach.